Effet de l’âge sur les variations de certains paramètres biochimiques chez les malades de sexe masculin atteints d’insuffisance rénale chronique (IRC). - SAIED, Assia (My University, 2023)
Chronic renal failure (CRI) is a major public health problem due to the progressive and irreversible decrease in the ability of the kidneys to perform their functions. Most often it is linked to diabetes and high blood pressure. The objective of this study is to follow the effect of age on the variations of certain biochemical parameters (urea, creatinine, glycemia, triglyceride and cholesterol) in this type of patient. The experiment was carried out on 63 CKD patients, male and divided into three age groups (40 to 60 years old, 60 to 70 years old and over 70 years old) each containing 21 subjects. Experimentation has shown clear alterations in certain biochemical parameters including glycaemia, uraemia, and creatinine, as well as dyslipidaemia, which is all the more accentuated with the age of patients suffering from CKD. These parameters can serve as biological markers of choice for the correct and early diagnosis of the disease.
Keywords: chronic renal failure (CRI); biochemical; dyslipidemia; age; parameters